2018
DOI: 10.3390/min8030086
|View full text |Cite
|
Sign up to set email alerts
|

Selective Attachment of Leptospirillum ferrooxidans for Separation of Chalcopyrite and Pyrite through Bio-Flotation

Abstract: Abstract:The replacement of depressants used in sulfide mineral beneficiation, with bacteria and their metabolites, promises to reduce the environmental impact left by the mining industry. In this study, the attachment of Leptospirillum ferrooxidans, L.f, to chalcopyrite and pyrite was investigated through Scanning Electron Microscopy (SEM). The impact of selective attachment, bacterial growth conditions, and extracellular polymeric substances (EPS) was investigated through bio-flotation. L.f exhibits selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Selective attachment on sulphidic minerals of the ore has been observed for Metallosphaera hakonensis [56] and for bioleaching microorganisms [2]. The bioleaching microorganism Leptospirillum ferrooxidans was preferentially attached to pyrite over chalcopyrite resulting in biofilm formation on pyrite surface, but not on chalcopyrite surface [34]. Leptospirillum ferrooxidans was shown to have a higher affinity to chalcopyrite than to pyrite, which resulted in higher depression of chalcopyrite in flotation and better settling behavior [26].…”
Section: Attachment Of Microorganisms On Mineral Surfacementioning
confidence: 97%
See 1 more Smart Citation
“…Selective attachment on sulphidic minerals of the ore has been observed for Metallosphaera hakonensis [56] and for bioleaching microorganisms [2]. The bioleaching microorganism Leptospirillum ferrooxidans was preferentially attached to pyrite over chalcopyrite resulting in biofilm formation on pyrite surface, but not on chalcopyrite surface [34]. Leptospirillum ferrooxidans was shown to have a higher affinity to chalcopyrite than to pyrite, which resulted in higher depression of chalcopyrite in flotation and better settling behavior [26].…”
Section: Attachment Of Microorganisms On Mineral Surfacementioning
confidence: 97%
“…The adhesion of Leptospirillum ferrooxidans cells on chalcopyrite and pyrite caused flocculation of both minerals [33]. Acidithiobacillus ferrooxidans had a depressive effect on pyrite [26] and Leptospirillum ferrooxidans on chalcopyrite [34].…”
Section: Sulphur-and Iron-oxidizing or Reducing Microorganismsmentioning
confidence: 99%
“…A modified Leptospirillum HH was used for growing L. ferrooxidans [63]. On the other hand, the best separation was obtained when L. ferrooxidans grew on chalcopyrite [73]. The contradictory flotation results between the different studies [63,73] might be due to their different methods of growing L. ferrooxidans.…”
Section: Leptospirillum Ferrooxidansmentioning
confidence: 99%
“…Extracellular polymeric substances (EPS) derived from L. ferrooxidans were found to be more effective than the L. ferrooxidans cultures [73]. Thus, improved chalcopyrite recovery and greater depression of pyrite was achieved with the use of EPS extracted from L. ferrooxidans.…”
Section: Leptospirillum Ferrooxidansmentioning
confidence: 99%
“…In 1999, American scholars (Zheng et al, 1999) studied the flotation separation of apatite and dolomite with anionic collector in the presence of Mycobacterium phlei (M. phlei), and found that M. phlei strains can be used as inhibitors of these two minerals, and the inhibitory effect on dolomite is better than that on apatite. Bleeze et al (2018) studied the extracellular polymeric substance (EPS) extracted from Leptospirillum ferrooxidans, grown on chalcopyrite for 48 hours, and polysaccharide-rich EPS selectively attaches to pyrite within 48 h, depressing its floatability and ensuring successful separation with a PIPX collector, resulting in Cu recovery of 95.8%. Natarajan et al ( 2001) used Bacillus polymyxa as a collector and found that its metabolites can change the surface properties of quartz and kaolinite and increase the floatability of quartz and kaolinite.…”
Section: .Introductionmentioning
confidence: 99%